2014
DOI: 10.1590/1516-1439.294614
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of thin bifacial silicon solar cells with locally diffused and selective back surface field

Abstract: The aim of this work is to present the development and comparison of thin n + pp + industrial bifacial silicon solar cells produced with the local screen-printed Al back surface field (BSF) to those with the selective BSF doped with aluminum-boron. To produce solar cells with selective BSF, the boron diffusion based on spin-on dopant was introduced in the process sequence. The thin SiO 2 layer (10 nm) thermally grown did not produce good passivation on the rear face and wafers were contaminated during aluminum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
0
3
0
7
Order By: Relevance
“…26) In contrast, a bifacial n-type monocrystalline Si cell also includes a Ag finger electrode on the rear surface for collecting the current generated by reflected light. 27) If the contact resistance between the rear finger electrode and the Si cell can increase due to the production of acetic acid gas by the hydrolysis of EVA, the degradation of the bifacial cell can be more accelerated than that of the monofacial cell after the DH test. However, the test result was different from the above estimation.…”
Section: Resultsmentioning
confidence: 99%
“…26) In contrast, a bifacial n-type monocrystalline Si cell also includes a Ag finger electrode on the rear surface for collecting the current generated by reflected light. 27) If the contact resistance between the rear finger electrode and the Si cell can increase due to the production of acetic acid gas by the hydrolysis of EVA, the degradation of the bifacial cell can be more accelerated than that of the monofacial cell after the DH test. However, the test result was different from the above estimation.…”
Section: Resultsmentioning
confidence: 99%
“…The source of acceptor dopant was boric acid H 3 BO 4 . Although references (Yadav et al , 2015; Singh et al , 2014; Moehlecke et al , 2014) have reported the process of BSF fabrication based on boric acid, all of them made use of the spin-on method (not the spray-on method). Preparation of solutions for spray-on application method with two different dopant concentration values was tested and their properties were examined: dopant solution 1 (DS1) containing 7.5 g of boric acid H 3 BO 4 ; and dopant solution 2 (DS2) containing 10 g of boric acid. …”
Section: Resultsmentioning
confidence: 99%
“…A malha metálica frontal foi implementada por serigrafia utilizando a pasta de prata PV159, da DuPont. As pastas foram secadas em forno de esteira a 200 °C e queimadas no mesmo forno, a 840 °C para lâminas sem camada de SiO 2 e 850 °C para lâminas com SiO 2 [14]. No processo de queima, a pasta de prata perfura as camadas de SiO 2 e TiO 2 , contatando eletricamente a região n + e a pasta de alumínio perfura a camada de SiO 2 , formando a região de BSF e o contato posterior.…”
Section: Materiais E Métodosunclassified
“…Com estrutura n + p, superfície frontal e posterior passivada com SiN x e região de BSF de Al localizada somente no contato elétrico da face posterior, foram obtidas as eficiências de 14,6%/13,6% (frontal/posterior) em dispositivos de área reduzida (4 cm 2 ) e com lâminas de silício Cz de 140 μm de espessura [13]. Regiões de BSF seletivo também foram propostas para células solares bifaciais fabricadas em lâminas finas [14,15]. No BSF seletivo, o boro é difundido em toda a face posterior e o Al somente no contato metálico em forma de malha, conforme esquematizado na Fig.…”
Section: Introductionunclassified
See 1 more Smart Citation